Discovery of an evodiamine derivative for PI3K/AKT/GSK3β pathway activation and AD pathology improvement in mouse models - Pang, Shuo; Li, Siyuan; Cheng, Hanzeng; Luo, Zhuohui; Qi, Xiaolong; Guan, Feifei; Dong, Wei; Gao, Shan; Liu, Ning; Gao, Xiang; Pan, Shuo; Zhang, Xu; et al. (Frontiers in Molecular Neuroscience, 2023)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by progressive neurodegeneration and cognitive decline. It was found that evodiamine could improve the learning cognitive impairment in AD model mice with the intensive study of the composition of Chinese medicine. However, evodiamine has high cytotoxicity and poor bioactivity. In this study, a range of evodiamine derivatives were designed and synthesized via heterocyclic substitution and amide introduction and screened for cytotoxicity and antioxidant capacity. Compared with the same concentration of evodiamine, we found that compound 4c displayed lower cytotoxicity and higher activity against H2O2 and amyloid  oligomers (AβOs) in vitro and significantly improved the working memory and spatial memory of 3×Tg and APP/PS1 AD mice. Subsequent RNA-seq and pathway enrichment analysis showed that 4c affected AD-related genes and the AMPK and insulin signaling pathways. Furthermore, we confirmed that 4c recovered the dysfunction of PI3K/AKT/GSK3β/Tau in vivo and in vitro. In conclusion, 4c represents a potential lead compound for AD therapy based on recovery of PI3K/AKT/GSK3β pathway dysfunction.